Vibrational Properties Calculation of Various Modeled Bacteriochlorophyll-a Molecules - Acharya, Dhaniram; Lamichhane, Hari Prasad (Journal of Institute of Science and Technology, 2015)
Density functional theory has been used to calculate normal mode infrared stretching vibrational frequencies and intensities of neutral as well as cationic modeled bacteriochlorophyll molecules. For bacteriochlorophyll-a, the calculated IR absorption band position for neutral and cation states of Bchl-a1 and Bchl-a2 structures have well matched with the published experimental results. Bacteriochlorophyll models having 133-ester C=O and 131-keto C=O have both symmetric as well as antisymmetric vibration in neutral state. Symmetric mode of vibration has higher frequency and lower intensity whereas antisymmetric mode has slightly lower in frequency and higher in intensity. However, in cation formation, the 131-keto and 133-ester vibrations decoupled and 131-keto mode has higher frequency having intensity nearly double than that of 133-ester C=O mode. This observation of frequency upshift and IR intensity change of various carbonyl groups of Bacteriochlorophyll-a4 model molecule upon cation formation is a strong reasoning to explain the experimental difference spectra of bacteriochlorophyll-a dimer in purple bacteria reaction centre (Leonhard & Mantele, 1993, Breton et al. 1999). Journal of Institute of Science and Technology, 2015, 20(2): 94-100